On Non-Vacuum Static Spherically Symmetric Solution in f(R) Theory of Gravity in V_5 - P. O. Bagde; K. T. Thomas (International Journal of Mathematics And its Applications, 2015)
In this paper, we studied non-vacuum static spherically symmetric solution of the field equation in metric gravity using dust matter and constant Ricci scalar curvature in five-dimensions. The density of dust matter and the function of the Ricci scalar curvature will also be evaluated at constant scalar curvature.